Faktor-Faktor yang Berperan dalam Cyberbullying Remaja di Media Sosial: Literatur Review - Putu Yuris Audia Mahadyasa; Ni Made Swasti Wulanyani (Journal on Education, 2024)
Cyberbullying is a behavioral deviation committed by adolescents through virtual media. One of the negative impacts feared for victims is the tendency to end their life. Based on a literature review, this study aims to describe several factors that play a role in adolescent cyberbullying on social media. This study uses a literature review approach to previous studies. The search uses Google Scholar, Garuda, and Neliti by looking for the year of publication of the journal 2017–2022. Based on 10 selected journal articles, factors that play a role or cause cyberbullying behavior in adolescents include parenting style, the intensity of using gadgets and using social media, moral models, perceptions of anonymity, conformity, callous unemotional traits, and internal motivation in the form of anonymous threats, envy, fun, and humiliation. Cyberbullying is a repeated bullying activity through digital technology that can harm victims physically, psychologically, and psychosocially, so it is necessary to know the causes of cyberbullying behavior as a first step in preventing it.